Ensuring the Effectiveness of Professional Training of Students Who Receive Design training in the Process of Teaching Computer Graphics (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article examines the methods used to ensure the effectiveness of professional training of students studying in the design direction in the process of teaching computer graphics and the research carried out in this direction.